Motor skills in children with ADHD: overlap with developmental coordination disorder - Emily J. Meachon; Julian P. Schaider; Georg W. Alpers (BMC Psychology)
Abstract Individuals with Attention-Deficit/Hyperactivity Disorder (ADHD) often have overlooked motor difficulties which can be at least partially attributed to co-occurring conditions such as Developmental Coordination Disorder (DCD). Understanding the influence of DCD and motor difficulties is important to detect in children for early support. Accordingly, the present study examined the prevalence of DCD diagnoses, cases of probable DCD, and related impairments among German-speaking parents of children with ADHD. A total of N = 168 parents completed an online study about their child’s potential for co-occurring DCD via the Developmental Coordination Disorder Questionnaire (DCD-Q). Even after children with DCD diagnoses were removed from the sample (n = 46), a majority still remained below threshold for probable DCD (55.9%) according to parent-reports. Via exploratory analyses, we also found that a majority of parents in the sample had not heard of DCD before (64.9%) and that many parents did not deem DCD as relevant to their children, even when their DCD-Q scores were in the range of probable DCD. The results align with a high prevalence of DCD in children with ADHD despite a simultaneous lack of awareness of DCD. Furthermore, findings in our sample align with frequently estimated global co-occurrence rates of 50% between ADHD and DCD. Broadly, the results support that motor difficulties should be considered in ADHD assessment and intervention.